2015
DOI: 10.1038/srep12963
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and Dynamic Coordination between Src Activity and Cell Protrusion in Microenvironment

Abstract: Migration of endothelial cells is essential for wound healing and angiogenesis. Src kinase activity plays important roles at the protrusions of migrating endothelial cells. However, the spatiotemporal coordination between Src kinase activity and the protrusion of cell edge remains unclear. Therefore, we investigate these coordinated molecular events at the initiation of cell migration, by integrating microfabrication, fluorescence resonance energy transfer (FRET)-based biosensors, and automated computational i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…We also found that KLF5 knockdown dramatically inhibited cell protrusion stimulated by EGF treatment (100 ng·mL −1 , 10 min) in 5637 cells (Fig. S1), suggesting that KLF5 involved in the regulation of the pathways related to cell protrusion, such as Src kinase family . Moreover, we calculated lamellipodia number and migration rate of 5637 cells in living cell imaging video, and confirmed that KLF5 knockdown decreased both lamellipodia number and migration rate of 5637 cells (Fig.…”
Section: Resultssupporting
confidence: 65%
“…We also found that KLF5 knockdown dramatically inhibited cell protrusion stimulated by EGF treatment (100 ng·mL −1 , 10 min) in 5637 cells (Fig. S1), suggesting that KLF5 involved in the regulation of the pathways related to cell protrusion, such as Src kinase family . Moreover, we calculated lamellipodia number and migration rate of 5637 cells in living cell imaging video, and confirmed that KLF5 knockdown decreased both lamellipodia number and migration rate of 5637 cells (Fig.…”
Section: Resultssupporting
confidence: 65%
“…S3a ) and evidenced in our previous publications 34 35 . Cross-correlation analysis 18 32 was performed to evaluate the temporal phase difference between FA structural changes and kinase activation ( Fig. 4e ).…”
Section: Resultsmentioning
confidence: 99%
“…While subcellularly targeted FRET biosensors enable the visualization of molecular signals with high resolution, computational analysis is indispensable for integrating multiple signals and deciphering regulatory parameters from live-cell images 18 23 31 32 . To elucidate the dynamic coupling between the biochemical kinase activities and structural FA dynamics we integrated the new FA-targeting biosensors, single-FA tracking, and cross-correlation analysis methods to quantitatively evaluate the temporal coordination of these molecular events at the single-FA level.…”
mentioning
confidence: 99%
“…The features for each ROI are the number of ROIs, the area of the ROI, angle of the ROI from major axis to the x-axis, and the duration time, which is the length in x-axis converted to time unit. Since there is no standard definition of a protrusion/retraction region, we asked multiple users to select the ROIs for the same heatmap, similar to refs 35,45,47 and 48. We then performed a one-way ANOVA test amongst all users to check reproducibility and found the p-value larger than 0.05, which indicated the selection among different users was similar.…”
Section: Methodsmentioning
confidence: 99%